Signs in science : despair and emptiness. - Tham, Tammy Samantha. (2009)
Never Let Me Go, The Stone Gods, The Possibility Of An Island are texts that demonstrate a world created by means of the non-real. This process is best understood if we approach the texts through Jean Baudrillard’s three orders of simulacra: imitation, production and simulation. The characters experience intensified fragmentation and loss when they become aware that they live in a world of simulation. The result is a pessimistic outlook of the future.